2021
DOI: 10.21037/atm-21-2508
|View full text |Cite
|
Sign up to set email alerts
|

Experimental animal models of drug-induced sensorineural hearing loss: a narrative review

Abstract: This narrative review describes experimental animal models of sensorineural hearing loss (SNHL) caused by ototoxic agents.Background: SNHL primarily results from damage to the sensory organ within the inner ear or the vestibulocochlear nerve (cranial nerve VIII). The main etiology of SNHL includes genetic diseases, presbycusis, ototoxic agents, infection, and noise exposure. Animal models with functional and anatomic damage to the sensory organ within the inner ear or the vestibulocochlear nerve mimicking the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 178 publications
(199 reference statements)
0
17
0
1
Order By: Relevance
“…Similar to the ototoxicity of aminoglycoside antibiotics and cisplatin, OP exposure resulted in morphological alterations in cochlea, threshold elevation, and prolongation of the interpeak latencies. However, the effects of OPs-induced hearing loss on experimental animals may be affected by animal species, dose, duration, and delivery route of agents (98). The exposure route in animal experiments could be different in humans, leading to an inconsistent outcome.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Similar to the ototoxicity of aminoglycoside antibiotics and cisplatin, OP exposure resulted in morphological alterations in cochlea, threshold elevation, and prolongation of the interpeak latencies. However, the effects of OPs-induced hearing loss on experimental animals may be affected by animal species, dose, duration, and delivery route of agents (98). The exposure route in animal experiments could be different in humans, leading to an inconsistent outcome.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…As such, the possible mechanism that can explain the reason of OAE absent but CM can be recorded are as follow: (a) OAE is more sensitive to the damage of OHCs 12 . Previous studies have shown that DPOAE has changed before the change of CM when no obvious structural change is found by electron microscopy 16,17 . When the OHCs have a certain degree of damage, OAE cannot be elicited but CM can be elicited.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Previous studies have shown that DPOAE has changed before the change of CM when no obvious structural change is found by electron microscopy. 16 , 17 When the OHCs have a certain degree of damage, OAE cannot be elicited but CM can be elicited. CM may be derived from residual OHCs and IHCs, as the function of IHCs may be preserved when the lesion site of AN is synapse or postsynaptic, although its contribution to CM is minimal (15%–20%).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other ototoxic drugs including doxorubicin (DOXO), aromatic solvent, ouabain, glutamic acid, glutamate analogues, 2-hydroxypropyl-β-cyclodextrin (HPβCD), and heavy metals also contribute to ototoxic drug–induced SNHL. 33 Kyle et al 34 reported that aspirin has a dose-dependent ototoxic side effect in elderly people, but the damage is reversible. Sensory hair cells undergo necroptosis and apoptosis after exposure to ototoxic drugs.…”
Section: Causes Of Snhlmentioning
confidence: 99%